ANALYSIS OF THE IMPACT OF MULTIMODAL MARITIME TRANSPORTATION EFFICIENCY ON EXPORT IMPORT LOGISTICS COSTS - Marleny Syam (Jurnal Penelitian Samudra, 2026)
High logistics costs remain a major challenge in supporting export-import competitiveness, particularly in archipelagic countries that rely heavily on maritime transportation. One strategic approach considered capable of reducing logistics costs is the implementation of a multimodal maritime transportation system that is effectively integrated with other modes of transportation. This study aims to analyze the impact of increasing the efficiency of multimodal maritime transportation on export-import logistics costs, focusing on key implementation factors, the current state of multimodal system efficiency, and integration barriers that cause cost inefficiencies. The research method used was a literature review of various scientific journals, research articles, international agency reports, and relevant academic publications published between 2020 and 2025. The analysis was conducted using a content analysis approach to identify patterns, key findings, and gaps in previous research. The results of the study indicate that the efficiency of multimodal maritime transportation is significantly influenced by the level of intermodal infrastructure integration, institutional coordination, regulatory harmonization, logistics system digitalization, and port operational performance. However, various previous studies have also revealed significant obstacles, such as limited supporting infrastructure, policy fragmentation, low interoperability of information systems, and weak coordination between stakeholders, which have resulted in increased logistics costs and delivery times. This study concludes that optimizing the multimodal maritime transportation system plays a strategic role in reducing export-import logistics costs, but requires an integrated and sustainable policy approach. The findings of this study are expected to provide a conceptual basis for formulating transportation and logistics policies and serve as a reference for further empirical research.